Female Drone Pilots: moving from an exception to the rule in Tanzania - Funja, Rose (Technical Centre for Agricultural and Rural Cooperation, 2019)
A young African woman thriving and growing her business in the male dominated field of drone piloting and data science. Rose Funja is also giving back by working to promote young womens' participation in STEM.